HUBUNGAN TEMAN SEBAYA DENGAN PERUBAHAN PERILAKU MEROKOK PADA SISWA SD NEGERI DAERAH AMPLAS - Vany Silvia Sabillah; Rini Deby Astria Lubis; Nur’ainun Berutu (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2022)
smoking behavior that is still very much done by adults that makes minors curious so that there is a feeling of wanting to follow the example.although there are many advertisements for cigarette sales that are usually posted in the mass media that appear to be elements of smoking ingredients and even images due to smoking, but still the public still ignores it. Indonesia still positions itself as the number 2 largest smoker in the world. to conduct an overview of the observation of smoking behavior on elementary school children and to find out the purpose and description of the causes of smoking behavior in elementary school children. This type of research uses quantitative methods with descriptive questionnaires and interviews the picture obtained based on questionnaires and interview methods is in school-age children who are caused by very large curiosity have a large percentage caused by cigarette advertisements of friend invitations etc. . Knowledge is the dominant factor predicting the smoking behavior of adolescents in Sandpaper. Researchers want to know the effectiveness of health education through the media of regional language cigarette brochures with cigarette knowledge in elementary school students in Amplas.